Solutions of initial value problems for a pair of linear first order ordinary differential systems with interface-spatial conditions. (1996) - Venkatesulu, M.; Baruah, Pallav Kumar
Abstract : Solutions of initial value problems associated with a pair of ordinary differential systems ( L 1, L 2 ) defined on two adjacent intervals I 1 and I 2 and satisfying certain interface-spatial conditions at the common end (interface) point are studied.